The usage of mobile application to teach practical skills among catering students - Md Sahak, Adibah Aishah; Md Yunus, Melor; Abdul Rahman, Abdul Wafi; Harun, Hairuddin; Marwanti, Marwanti; Tukiran, Nor Anis Intan Aqiah (Faculty of Engineering, Universitas Negeri Yogyakarta, 2019)
Latest educational media based on mobile application nowadays is an important tool for teaching and learning which can help to attract the students’ attention and the students will be more efficient since they can study by their own anywhere and anytime with different situations surround them. This paper focuses on the usage of the mobile application in teaching practical skills among catering students. In line with the issues nowadays where the live demonstration is too backdated rather than use the mobile application to enhance the enjoyment of the cooking process in catering classroom. Teaching and learning with the mobile application was perceived to assist the learning process in cooking by following ways: increasing the comprehension of the cooking process and real-time to reassurance in the cooking process, enhancing the enjoyment of the cooking process and acquire new cooking skills. The findings show that the usage of mobile application is at moderate level. On the other hand, the positive implication towards students is at medium level. Overall, for this study, researchers found that the usage of mobile application among catering students was good and perceived positively towards students.